Metabolic impact of glutaminase isoenzymes modulation on glioma cell lines - De los Santos-Jiménez, Juan; Rosales, Tracy; Bookyung, Ko; Márquez-Gómez, Javier; DeBerardinis, Ralph J; Mates-Sánchez, José Manuel (My University, 2022)
Many tumors use glutamine for both energy generation and as a biosynthetic precursor. Glutaminases (GAs) catalyze the first step of glutaminolysis by converting glutamine (Gln) into glutamate and ammonia in the mitochondria. In humans, two genes encode for glutaminases: GLS and GLS2. GLS is widely considered as a tumor promoting gene and encodes two isoforms named KGA and GAC, and is usually overexpressed in many tumors. On the other hand, GLS2 encodes isoforms GAB and LGA, and appears to have more complicated roles, including tumor-suppressive functions in some contexts. In glioma, GLS2 is commonly silenced and GLS is usually overexpressed. We examined the metabolic consequences of inhibiting GLS activity in three glioma cell lines (LN229, T98G and U87MG) by using the clinically relevant inhibitor CB-839, or expressing GLS2, by generating a glioma cell model overexpressing GLS2 (LN229-GLS2), otherwise silenced. Both experimental conditions were analyzed by using a metabolomics approach for metabolite levels quantification in an Agilent Quadrupole Time of Flight LC-MS. We also performed stable isotope tracing experiments using U-13C-labeled Gln and 15N-labeled Gln in the amido group to ascertain the metabolic fates of Gln carbon and nitrogen. Briefly, metabolomics and carbon tracing results showed that CB-839 treatment depleted tricarboxylic acid cycle (TCAC) intermediates, while GLS2 maintained those pools, even upon concomitant GLS inhibition by CB-839. Results also showed that GLS inhibition by CB-839 and GLS2 expression had a remarkable effect on nucleotide de novo biosynthesis and also affected overall methylation patterns.
Keywords: Cáncer - Metabolismo; glutaminase; CB-839; GLS2; Metabolomics; Glutaminase; Glioblastoma